(3GdJHUjQ aj GdOjf hJejjR GdaQbI GdfGLjI Yf GdaQb GdgGdcjfs - (3CHh GdeXaQ WGgQ Hf eMeO GdESaQGjjfj,J (B471 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO efg bhdg (B: (3ai JaVjd ebGdGJ GdQhGaV hHjGf aVGFMge GdHGH GdQGHY ai HjGf ebGdGJ GdNhGQL hHjGf aVGFMge s
(3BNQgG (B:s
(3hQhGJg CNQi jTaY cd hGMO efge YOO QHjYI heVQ hdG JLYd ai bdhHfG ZdG ddPjf BefhG QHfG Efc QDha QMje s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B223s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds